A high-resolution map of synteny disruptions in gibbon and human genomes. - Lucia Carbone; Gery M Vessere; Boudewijn F H ten Hallers; Baoli Zhu; Kazutoyo Osoegawa; Alan Mootnick; Andrea Kofler; Johannes Wienberg; Jane Rogers; Sean Humphray; Carol Scott; R Alan Harris; et al. (PLoS Genetics, 2006)
Gibbons are part of the same superfamily (Hominoidea) as humans and great apes, but their karyotype has diverged faster from the common hominoid ancestor. At least 24 major chromosome rearrangements are required to convert the presumed ancestral karyotype of gibbons into that of the hominoid ancestor. Up to 28 additional rearrangements distinguish the various living species from the common gibbon ancestor. Using the northern white-cheeked gibbon (2n = 52) (Nomascus leucogenys leucogenys) as a model, we created a high-resolution map of the homologous regions between the gibbon and human. The positions of 100 synteny breakpoints relative to the assembled human genome were determined at a resolution of about 200 kb. Interestingly, 46% of the gibbon-human synteny breakpoints occur in regions that correspond to segmental duplications in the human lineage, indicating a common source of plasticity leading to a different outcome in the two species. Additionally, the full sequences of 11 gibbon BACs spanning evolutionary breakpoints reveal either segmental duplications or interspersed repeats at the exact breakpoint locations. No specific sequence element appears to be common among independent rearrangements. We speculate that the extraordinarily high level of rearrangements seen in gibbons may be due to factors that increase the incidence of chromosome breakage or fixation of the derivative chromosomes in a homozygous state.